Community Perceptions of Online Religious Authority: A Qualitative Study among Urban Muslim Communities - Ningsih, Widia (Islamic Journal of Communication and Public Discourse, 2025)
Digital transformation has created a new space for religious authority formation, encouraging the emergence of online religious figures that influence urban Muslim communities. This study aims to understand the perceptions of urban Muslim communities regarding online religious authority and to identify the factors that influence their acceptance or skepticism of online religious figures. Using a qualitative approach with a phenomenological method, data were collected through in-depth interviews with 30 respondents from Jakarta, Bandung, and Surabaya, and analyzed using thematic analysis techniques assisted by NVivo 14. The results show that perceptions of online religious authorities are selective and contextual; 40% of respondents trust traditional clerics more, 25% accept online preachers, 20% show skepticism, and 15% adopt situational trust. Factors such as educational background, communication skills, openness, and consistency of teachings are key in building trust. This research highlights the importance of strengthening digital literacy in the realm of religion. It underscores the need for an online preaching certification program to maintain the credibility of the digital space. The findings make a crucial contribution to understanding the dynamics of religious authority in the digital era and form the basis for developing effective da'wah strategies that are relevant to the needs of contemporary urban Muslim communities.